Isolation and Characterization of Regulators of Oxidative Stress-Induced Apoptosis in Yeast. - Fireizen, Yaron; Crozier, Christine (My University, 2009)
This project is a long-term project aimed at identifying possible mechanisms that connect the oxidative stress pathway to the apoptosis or cell death regulatory machinery in the budding yeast, S. cerevisiae. We have generated all the necessary yeast strains and gene expression systems, including a strain of yeast that expresses the mouse BCL-2 gene, an inhibitor of apoptosis.
Color poster with text and images.
Keywords: Saccharomyces cerevisiae; Yeast--Genetic engineering; Yeast fungi--Genetic engineering; Fungal gene expression; Posters